Deterrence by Diplomacy - Sartori, Anne E., 1966- (Book collections on Project MUSE., 2005)
"Deterrence by Diplomacy departs from traditional deterrence theory also in its implications about how states can increase the credibility of their threats. Traditional theory suggests that by fighting over small issues states can show resolve to fight over large ones. This book, which develops its arguments about effective diplomacy through a game-theoretic argument and tests the resulting implications using statistical analyses, points to an alternative road to credibility: states can make their threats more credible by sometimes honestly acquiescing when they do not consider the issues important enough to be worth a fight - in other words, by not crying "wolf.""--Jacket